FAKTOR-FAKTOR YANG MEMPENGARUHI KOMITMEN TENAGA PENGAJAR PERGURUAN TINGGI - Sutoro, Moh. (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
The main task of the lecturer is Tri Dharma. Then, the implementation must be accompanied by responsibilities, quality-oriented teaching, benefit-oriented research, and welfare-oriented service. To realize this requires an effort, and therefore this research was conducted to see what factors influence lecturer performance. The quantitative research method was chosen as a scientific way, by distributing questionnaires and analyzing with structural models. The results showed, performance is achieved through commitment, and motivation and other variables. This finding confirms that commitment plays an important role in realizing performance, even in reality other variables such as motivation, discipline, compensation and the environment are needed